Perceived changes in capability during the COVID-19 pandemic: A Swedish cross-sectional study from June 2020 - Upplevda förändringar i handlingsfriheter under COVID-19 pandemin: En svensk tvärsnittsstudie från Juni 2020 - Meili, Kaspar; Månsdotter, Anna; Lindholm, Lars (Umeå University, 2021)
Covid-19 has affected people in various ways, directly through disease and death, and indirectly through disease containment measures. Understanding how the pandemic and countermeasures agaist it impacted quality of life is valuable for policy makers.

To address and compare the various components of quality of life, a suitable framework is needed, which the capability approach provides. This approach measures quality of life as opportunities, compared to traditional welfarist economics that defines wellbeing as utility.

For this study, we used a capability list from a Swedish governmental investigation (SOU 2015:56) that suggested relevant capabilities for the Swedish situation: Financial situation, Social relations, Health, Housing, Living environment, Occupation, Knowledge, Security, Time balance, and Political and civil rights.

The study was performed in June 2020. In an internet-based survey, we quota-sampled 500 Swedish residents from a commercial web-panel, after population proportions of age, region of residence, education, gender.

The survey started with the informed consent statement, followed by questions on participants’ current baseline capability levels in the ten capability dimensions (Low, Medium, Complete). Next followed questions about perceived changes in capability during 2020 in the ten dimensions on a five-item Likert scale (Much less, Less, Equal, Higher, Much higher). The survey ended with a number of background questions on socio-economic and demographic conditions.

Sampling large numbers of participants using a commercial web panel is administratively more feasible and quicker than other sampling methods, such as for example direct sampling from the general population. Also, the response rate may be higher and data handling easier. On the other hand, it is less transparent how recruitment into the study was performed and web panel participants may not be representative of the population. Those limitations should be kept in mind when analysing the data and interpreting results.

Data were collected with a PHP-based web application for surveys (limesurvey version 4.2.2, https://www.limesurvey.org) hosted on a Umeå university server. The data was collected anonymously.

Covid-19-pandemin har påverkat samhället på olika sätt, direkt genom sjukdom och dödlighet, och indirekt genom smittskyddsåtgärdernas inverkan på skola, arbete, fritid osv. Förståelsen för hur pandemin och åtgärderna för att begränsa den har påverkat livskvaliteten kan vara betydelsefullt för beslutsfattare.

Men för att kunna beakta olika komponenter av livskvalitet på ett jämförbart sätt behövs det ett robust ramverk, vilket den så kallade "capability approach" erbjuder. Denna ansats mäter livskvalitet i termer av handlingsfriheter till skillnad från traditionell "welfaristisk" nationalekonomi som mäter välbefinnande i termer av "utility".

I denna studie utgår vi från en lista över tio handlingsfriheter som föreslogs av en statlig offentlig utredning (SOU 2015:56) att vara särskilt relevanta för den svenska kontexten: Ekonomisk situation, Sociala relationer, Hälsa, Boende, Närområde, Yrke, Kunskap, Säkerhet, Tids-balans, och Politiska fri- och rättigheter.

Studien genomfördes i juni 2020 genom en webbaserad enkät som distribuerades till ett urval av 500 individer i Sverige från en kommersiell webbpanel (Cint), efter kvot-stratifiering utifrån befolkningens ålder, region, utbildning och kön.

Enkäten inleddes med en fråga om informerat samtycke, följt av frågor om respondenternas nuvarande situation utifrån de tio handlingsfriheterna (låg, medium, hög). Därefter följde frågor om upplevda förändringar i handlingsfriheterna under 2020 (dvs. den största delen av perioden med covid-19-pandemin), på en Likertskala med fem svarsalternativ (mycket mindre, mindre, oförändrat, mer, mycket mer). Enkäten avslutades med ett antal bakgrundsfrågor om socioekonomiska och demografiska förhållanden.

Att ta stora stickprov från kommersiella webbpaneler är administrativt sett enklare och snabbare än andra metoder som till exempel att direkt ta ett allmänt befolkningsstickprov. Även svarsfrekvens kan vara högre och datahantering enklare. Å andra sidan är det mindre transparent hur studierekryteringen gick till och gruppen av webbpaneldeltagarna kanske inte är representativ för befolkningen. Dessa begränsningar borde behållas i minnet när man ska analysera data och tyda resultat.

Uppgifterna samlades med en PHP-baserad webapplikation för enkäter (limesurvey version 4.2.2, https://www.limesurvey.org) som drivs från en server vid Umeå universitet. Uppgifterna samlades in anonymt.
Upplevda förändringar i handlingsfriheter under COVID-19 pandemin: En svensk tvärsnittsstudie från juni 2020 - Perceived changes in capability during the COVID-19 pandemic: A Swedish cross-sectional study from June 2020
Keywords: economics; ekonomi; health; hälsa; welfare economics; välfärdsekonomi; public health; folkhälsa; social welfare philosophy; social välfärdsfilosofi; COVID-19; COVID-19; Extra-welfarism; Extra-welfarism; Capability approach; Capability approach; Health economics; Hälsoekonomi; General health and well-being; Allmän hälsa och välbefinnande; Social conditions and indicators; Sociala förhållanden och indikatorer; Health Care Service and Management, Health Policy and Services and Health Economy; Hälso- och sjukvårdsorganisation, hälsopolitik och hälsoekonomi; Economics; Nationalekonomi; Other Social Sciences not elsewhere specified; Övrig annan samhällsvetenskap; Philosophy; Filosofi; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin